The careers of British musicians, 1750-1850 : a profession of artisans - Rohr, Deborah Adams (Cambridge University Press, 2001)
The study of the social context of music must consider the day-to-day experiences of its practitioners. This book traces the daily working life and aspirations of British musicians during the sweeping social and economic transformation of Britain from 1750 to 1850.